Energy Efficient Development Model for Regions of the Russian Federation: Evidence of Crypto Mining - Meynkhard, Artur (International Journal of Energy Economics and Policy, 2019)
Paper proposes a model of energy efficient development of the regional energy complex, in which provided by mixing and iterative matching forecasts of energy consumption and energy production. The novelty of this method is that it formed in the framework of the regional model, is part of the overall regional product-sector balance formed for the region, which allows to simulate the mutual influence of energy complex and the rest of the economy through interbalance relations. Search for optimal solutions are carried out by iteration using a specially designed approach based on the Stiglitz-Sen-Fitoussi approach. It includes the following welfare components: economic well-being, non-monetary characteristic welfare and reproduction potential of the economy. System of crypto mining based on the evidence of proof-of-work protocol are extremely no energy efficient. Paper also gives evidence of Russian regions for mining of cryptocurrencies in Russia. Keywords: energy, resource saving, energy efficient development, energy indicators, forecasting JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.7759